(untitled) (Baghdad Science Journal, 2011)
The aim of this research is to determine the uranium concentration in soil and water samples taken from different locations from the middle and south of Iraq using fission fragments track registration. Twelve samples of soil and water were taken from middle and South of Iraq. The nuclear reaction used as a source of nuclear fission fragments is U-235 (n.f) obtained by bombardment U-235with thermal neutrons from (Am-Be) neutron source with flux (5X103 n.cm-2.s-1). The concentration values were calculated by a comparison with standard samples recommended by IAEA.The results of the measurements show that the uranium concentration in soil samples were in Thekar (16.38 ppm), AL-Basra (16.1ppm) and (0.78 ppm) in Baghdad, from the results which show that this governorate were contaminated with depleted uranium after the Wars against Iraq . The uranium concentration in the water samples of Tigers river were in AL-Qurna (8.85 ?g/l) and in AL-Suwera (4.72 ?g/l).